Improving nutrition in Haryana: Insights from examining trends in outcomes, determinants and interventions between 2006 and 2016 - George, Nitya Rachel; Nguyen, Phuong Hong; Avula, Rasmi; Menon, Purnima (International Food Policy Research Institute, 2017)
The purpose of this Policy Note is to examine the trends in undernutrition in Haryana as well as to document trends and geographic variability in the determinants of nutrition and the coverage of key nutrition and health interventions. In doing this analysis, we aim to highlight the key areas of action to improve nutrition in Haryana.